2023
DOI: 10.3390/lubricants11020065
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite Reinforced Natural Esters for Energy Applications

Abstract: Recently, environmentally friendly and sustainable materials are being developed, searching for biocompatible and efficient materials which could be incorporated into diverse industries and fields. Natural esters are investigated and have emerged as eco-friendly high-performance alternatives to mineral fluids. This research shows the evaluations on thermal transport and tribological properties of halloysite nanotubular structures (HNS) reinforcing natural ester lubricant at various filler fractions (0.01, 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Biomaterials based on vegetable oils offer a sustainable, biodegradable and low-cost alternative for various applications in engineering and biomedicine [191]. Taha-Tijerina et al found that halloysite nanotubular structures (HNSs) reinforcing natural ester lubricants significantly reduce the friction coefficient and wear scar diameter, offering environmentally friendly alternatives to mineral fluids for industrial applications [192]. Gupta et al focused their research on the development of ecological nano-lubricants, using mahua and linseed oils with h-BN nanoparticles as additives.…”
Section: Base Lubricantsmentioning
confidence: 99%
“…Biomaterials based on vegetable oils offer a sustainable, biodegradable and low-cost alternative for various applications in engineering and biomedicine [191]. Taha-Tijerina et al found that halloysite nanotubular structures (HNSs) reinforcing natural ester lubricants significantly reduce the friction coefficient and wear scar diameter, offering environmentally friendly alternatives to mineral fluids for industrial applications [192]. Gupta et al focused their research on the development of ecological nano-lubricants, using mahua and linseed oils with h-BN nanoparticles as additives.…”
Section: Base Lubricantsmentioning
confidence: 99%
“…Nanofluids and nanolubricants are engineered colloidal suspensions of nanostructures homogeneously dispersed within conventional fluids. The application of the nanofluids as coolants has shown significant improvements in the thermophysical characteristics, which is mainly due to the inclusion of reinforcing nanostructures and their molecular interaction among the base fluids and lubricants [12][13][14][15]. Nanofluids have attracted the interest of scientists and industry due to their superb thermal transport characteristics.…”
Section: Introductionmentioning
confidence: 99%